2019
DOI: 10.3390/nano9101365
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Nanoparticles and Biosystems: Microenvironment of Nanoparticles and Biomolecules in Nanomedicine

Abstract: Nanotechnology is a multidisciplinary science covering matters involving the nanoscale level that is being developed for a great variety of applications. Nanomedicine is one of these attractive and challenging uses focused on the employment of nanomaterials in medical applications such as drug delivery. However, handling these nanometric systems require defining specific parameters to establish the possible advantages and disadvantages in specific applications. This review presents the fundamental factors of n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(154 citation statements)
references
References 126 publications
3
151
0
Order By: Relevance
“…Temperature is a critical parameter in the formation of nanocrystal and also in the hydrolysis reaction of thioacetamide, because it plays an important role in the study of CdS. In this study, among the studied synthesis methods [26], it was observed that better synthesis yields are achieved at low temperature. In these cases, small CdS nanoparticles are obtained with high stability and fluorescence.…”
Section: Effect Of the Ph In The Medium On The Synthesis Of Cds-bsa Qdsmentioning
confidence: 79%
See 1 more Smart Citation
“…Temperature is a critical parameter in the formation of nanocrystal and also in the hydrolysis reaction of thioacetamide, because it plays an important role in the study of CdS. In this study, among the studied synthesis methods [26], it was observed that better synthesis yields are achieved at low temperature. In these cases, small CdS nanoparticles are obtained with high stability and fluorescence.…”
Section: Effect Of the Ph In The Medium On The Synthesis Of Cds-bsa Qdsmentioning
confidence: 79%
“…IVTT enables not only in situ transcription-translation of human proteins directly from cDNA, but also post-transcriptional and post-translational modifications (PTMs) such as phosphorylation and glycosylation, among others. Compared to other conventional protein expression systems, IVTT can produce functional properly folded proteins of any size in a less complex manner while still being a highly efficient procedure; in fact, it has been adopted as a useful strategy in the Human Proteome Project (www.hupo.org) [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of NP parameters, such as size, shape, charge, colloidal stability, corrosion, stiffness and so forth, on interactions with molecules, living cells and animal models has been researched. However, interfacing inorganic NPs with biological settings have led to the most influential and outstanding discoveries [130][131][132]. For that reason, even though inorganic NPs are not considered biomolecules, their multiple biomedical applications and the various advantages offered when combined with biocomposites has led the authors to open an exception and include them in this section.…”
Section: Nanoparticles (Nps)mentioning
confidence: 99%
“…Nanoparticle interaction with biological matrix is greatly affected by the morphology of the particle, surface chemistry, functionalization, and electronic and physicochemical properties. Understanding of biointerface science for nanoparticle and bio-matrix interaction mainly depends on particle size and surface characteristics [2].…”
Section: Extended Abstractmentioning
confidence: 99%